If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 26 = 44 Reorder the terms: 26 + 2x = 44 Solving 26 + 2x = 44 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + 2x = 44 + -26 Combine like terms: 26 + -26 = 0 0 + 2x = 44 + -26 2x = 44 + -26 Combine like terms: 44 + -26 = 18 2x = 18 Divide each side by '2'. x = 9 Simplifying x = 9
| 2x+10=x+36 | | 35-14=-35 | | 96+x=40x | | 5x+100=-235 | | -6s=36 | | y=(1-x)/1.2 | | (x+7)(x-2)=(x+1)(x+1) | | 1.4(x+1.2)=7.8 | | -24/5=31/2h | | (x+7)(x+2)=(x+1)(x+1) | | m=z+bx | | 12x+8y+7x=z | | 2(3x-4)+6(x-5)=-3(4-5x)+5x-16 | | 4y-1x+2y=z | | [8+(-4)]-5= | | -8/12-21/12 | | 12+[-5+(-4)]= | | (7/x)-(1/7)=(2/x) | | 3(3x-2)=15 | | 2(3x-5)+6(x-3)=-3(3-5x)+5x-1 | | 2-4(x+3)=4-2(3x+5) | | 2.5=2/s | | -2(-3)-5y=4 | | -2y-42=3(y+1) | | -2/3(6*3-45)-2(3) | | 9x+2x=0x | | 21-u=17 | | 3x^2-4y=7 | | 2/5*15-1=5 | | (6a+1)(5a+2)= | | 5x-(4x+5)=3x-33 | | 441800*8*5/12 |